A critical review on the fabrication processes and performance of polyamide biocomposites from a biofiller perspective. (September 2019) - Ogunsona, E.O.; Codou, A.; Misra, M.; Mohanty, A.K.
Abstract: While many fillers have been used to tailor the properties of polyamides, the incorporation of bio-based reinforcement has been limited because of their low thermal stability and the high processing temperature of polyamides. The objective of this review is to analyze the current knowledge on strategies aimed at improving and making natural fiber reinforced polyamide biocomposite fabrication viable with improved properties. A discussion on (bio-)polyamides is introduced, and critical factors affecting their mechanical properties during compounding with natural fibers are discussed. Benefits and limitations of each strategy employed are summarized with a discussion on the contributions to the final material performance, cost, and environmental impact. These strategies involved limiting the natural fibers thermal degradation via process control, material, and fiber modifications.